THE DIFFERENCE IN THE RESULTS OF CIRCULAR SKIRT FROM COTTON AND TAFFETA MATERIALS - Resi Sepsilia Elvera; Miftahurrahmi Miftahurrahmi (Sean Institute, 2023)
This research aims to know the difference in the results of circle skirts made of cotton and taffeta This research is a descriptive study with quantitative methods. The data collection method used an assessment format sheet by giving a check mark () and was assessed by 3 panellists from fashion design expert lecturers. The data analysis used was descriptive statistical techniques with percentage calculations using Microsoft Office Excel 2007 data. The results showed differences in the use of cotton and taffeta in circle skirts, namely that taffeta has waves that fall parallel to the diagonal direction. At the same time, cotton falls waves not too straight parallel to the diagonal direction. Balance the lower circumference of the hanging cotton skirt. Taffeta has bigger waves than cotton. The taffeta material forms an A-line silhouette for thin women for party occasions. Cotton material forms an H-line suitable for obese women for everyday wear, travelling and relaxing.